2016
DOI: 10.7863/ultra.15.04055
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Survival of Fetal Tetralogy of Fallot

Abstract: The postnatal outcomes, genetic testing results, and sonographic findings are different among subtypes of tetralogy of Fallot. Documenting those details at diagnosis can help specialists better counsel their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The reported rates of 22q11.2 deletion in TOF were varying from 0 to 18% [4, 16, 17]. A meta-analysis study demonstrated that 18.6% of fetal TOF was complicated with 22q11.2 deletion [18] and TOF with pulmonary stenosis was more frequently associated with major chromosomal anomalies, while 22q11.2 deletion syndrome occurred more common in fetal TOF with pulmonary atresia and TOF with an absent pulmonary valve syndrome [18]. In our series, prevalence rates of chromosomal anomalies and 22q11.2 deletion were not significantly different among TOF with pulmonary atresia, TOF with pulmonary stenosis and TOF with an absent pulmonary valve syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rates of 22q11.2 deletion in TOF were varying from 0 to 18% [4, 16, 17]. A meta-analysis study demonstrated that 18.6% of fetal TOF was complicated with 22q11.2 deletion [18] and TOF with pulmonary stenosis was more frequently associated with major chromosomal anomalies, while 22q11.2 deletion syndrome occurred more common in fetal TOF with pulmonary atresia and TOF with an absent pulmonary valve syndrome [18]. In our series, prevalence rates of chromosomal anomalies and 22q11.2 deletion were not significantly different among TOF with pulmonary atresia, TOF with pulmonary stenosis and TOF with an absent pulmonary valve syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This observed decline over time in mortality can be accounted for by several factors. Advances in prenatal diagnosis, that have enabled earlier detection of foetal anomalies [23, 28–31], specifically in Spain [32–34], plus advances in surgical intervention techniques [13, 14, 20, 35], also in Spain [36], are the main factors identified as being responsible for the decrease in mortality. In addition, this downturn has also been influenced by the implementation of and improvement in cardiac rehabilitation programmes [3739] coupled with ambulatory management and follow-up [40].…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have specifically analysed TOF patient mortality following surgical repair of the defect [11, 1315], others have focused on overall CHD mortality [1618]. In addition, some other TOF studies report on long-term outcome and survival analyses [1923].…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric fusion of the artery bulbar and truncal ridges resulting in anterosuperior displacement of the outlet septum generates tetralogy of Fallot 2 . The anterosuperior deviation of the outlet septum relative to the rest of the ventricular septum causes an anterior misalignment type of ventricular septal defect, pulmonary obstruction, overriding or dextroposition of the aorta, and right ventricular hypertrophy 7 . In addition to the main features, TOF is associated with other structural abnormalities 3 , such as a right aortic arch 5 , a deviated cardiac axis, an aberrant subclavian artery, and an absent ductus arteriosus 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This case of TOF with PA featured a right aortic arch with left ductus arteriosus connected between the dilated left innominate artery and subpulmonary arteries. A recent study reported prenatal TOF detection rates of only 30-60% 1 , and differentiation of TOF subtypes with unusual associated malformations is even more challenging 1,7 . Ignorance of this potential connection between dilated left innominate artery and subpulmonary arteries via left ductus arteriosus can lead to misdiagnosed as absent ductus arteriosus.…”
Section: Discussionmentioning
confidence: 99%